"Is All in All": Exploring Spirituality with People with Expressive Aphasia Using a Phenomenological Approach. (2nd January 2023) - MacKenzie, Sophie
Abstract: Although spirituality has been discussed extensively in the healthcare literature in general in the last twenty years, there is a paucity of speech and language therapy literature related to the subject. Spiritual concerns may be brought to the fore and need to be expressed after serious illness. However, following stroke, some patients may present with difficulties in their communication, such as aphasia. This research asks the following research question: what is it like to express your spirituality when you have aphasia? Eight people with aphasia were interviewed about their spirituality using a phenomenological approach. The interviews were transcribed and analyzed using a flexible analytic approach, and themes common to several participants were identified. Participants were able to express ideas of spirituality and life-meaning using a variety of communication methods. Speech and language therapists need to be mindful of their patients' spiritual concerns if therapy is not to become superficial.